Introductory microeconomics - Pagoso, Cristobal M.; Dinio, Rosemary P. ; Villasis George A. (Manila, 2006)
This book is designed for undergraduate courses in basic microeconomics, economic analysis or the theory of price and output determination, value and distribution... -- Preface
Keywords: Microeconomics